MACROINVERTEBRATES - Jongkar, Grinang; Brian Haessler, Delim; Lee, Nyanti; Ling, Teck Yee; Sim, Siong Fong; Tonny, Ganyai; Lee, Karen Suan Ping (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd, 2021)
The drainage system of the Pelagus area comprises first to sixth order streams, with slow to fast flowing water and moderate gradient channels. The tributaries are important feeder streams in sustaining hydrological functions of the main Rajang River, especially as a result of the construction of two hydroelectric dams in the upper stream, the Bakun Dam and Murum Dam. Macroinvertebrates sampling was conducted twice at 27 tributaries between 2013 and 2016. Three replicates of kick-net sampler (30 × 32 cm, 400-micron mesh size) were made for each visit, yielding a total of 162 samples. Hand collecting at night along riverbanks and forest trails was carried out for semiterrestrial crabs. Specimens caught from local fishing tools, such as castnet (‘jala’) and traps (‘bubu’) were also recorded. The multiple sampling techniques used have produced a macroinvertebrate inventory for the Pelagus area, which shows over 79 species in 52 families and 12 orders, comprising aquatic insects, crustaceans, molluscans and aquatic worms. All crabs and some taxa of aquatic insects are endemic to Borneo. Macroinvertebrates were assigned to functional feeding groups, and field observations of species occurrence on major substrate types were recorded.